Prediction model for psychological disorders in ankylosing spondylitis patients based on multi-label classification - Yang, Kun; Gong, Yifan; Xu, Xiaohan; Sun, Tiantian; Qu, Xinning; He, Xiaxiu; Liu, Hongxiao (Frontiers in Public Health, 2025)
ObjectiveThis study aims to develop a predictive model to assess the likelihood of psychological disorders in patients with ankylosing spondylitis (AS) and to explore the relationships between different factors and psychological disorders.MethodsPatients were randomly divided into training and test sets in an 8:2 ratio. The Boruta algorithm was applied to select predictive factors, and a multi-label classification learning algorithm based on association rules (AR) was developed. Models were constructed using Random Forest (RF), K-Nearest Neighbor (KNN), RF-AR, and KNN-AR, and their performance was assessed through receiver operating characteristic (ROC) curves on the test set.ResultsA total of 513 AS patients were included, with 410 in the training set and 103 in the test set. The Boruta algorithm identified five key variables for the model: fatigue, ASAS-HI score, disease duration, disease activity, and BMI. The RF-AR model performed best, with an accuracy of 0.89 ± 0.06, recall of 0.78 ± 0.1, F1-score of 0.86 ± 0.08, Hamming loss of 0.05 ± 0.03, and a Jaccard similarity coefficient of 0.75 ± 0.12. The area under the curve (AUC) for the training set was 0.94.ConclusionThis study developed a predictive model for assessing the risk of psychological disorders in AS patients. The model effectively captures the presence of psychological disorders, providing clinicians with valuable insights for adjusting treatment strategies.